Getting a Home for Urban Young Adult: A preliminary study of intergenerational housing transitions in Indonesia - 'Ul Jannah, Annissa; Adianto, Joko (International Journal of Built Environment and Scientific Research, 2024)
Each generation has its own challenges in the journey to get a home. This study aims to understand how the housing transition is experienced by three different generations (boomer, generation X, millennial, and generation Z) within parent-child relationship, especially during the young adult period and when entering the home ownership market in urban area in Indonesia. Using in-depth interviews, this research explores the housing transition stories of people who have a child-parent relationship (n=4), consisting of 2 men and 2 women in Indonesia. The findings from this study are that the life course in the form of entering marriage is the main driving factor in the housing transition in both generations. In the second generation, assistance in the form of motivation and financial assistance from parents plays a major role in their home transition. Individuals' housing preferences may also be factors that influence the way they choose a home when entering the home ownership market.